Low field strength magnetic resonance imaging of the neonatal brain. Issue 3 (1st May 2003) - Whitby, E H; Paley, M N; Smith, M F; Sprigg, A; Woodhouse, N; Griffiths, P D
Abstract : Background: Magnetic resonance (MR) imaging of the neonate has been restricted by the need to transport the sick baby to the large magnetic resonance scanners and often the need for sedation or anaesthesia in order to obtain good quality images. Ultrasound is the reference standard for neonatal imaging. Objective: To establish a dedicated neonatal MR system and compare the clinical usefulness of MR imaging with ultrasound imaging. Design: Prospective double blind trial. Setting: Neonatal intensive care unit, Sheffield. Main outcome measures: Imaging reports. Patients: 134 premature and term babies. Results: In 56% of infants with pathology suspected on clinical grounds, MR provided additional useful clinical information over and above that obtained with ultrasound. Conclusion: Infants can be safely imaged by dedicated low field magnetic resonance on the neonatal intensive care unit without the need for sedation at a cost equivalent to ultrasound.